A conceptual model of individual identifications in the context of coopetition. (1st January 2014) - Näsholm*, Malin H.; Bengtsson, Maria
Individuals working on inter-organisational cooperative projects with their competitors are important to the success of a coopetitive relationship between firms, but the role of individuals has rarely been addressed in coopetition research. The purpose of this paper is to develop a conceptual model of individuals in coopetitive contexts and explore their identification with the organisation and the cooperative project. The developed model links experienced coopetition to individuals' dual, potentially conflicting, identifications which affects individuals' experienced tension and coopetitive behaviour. Secondly we will discuss how these consequences of coopetition for individuals affect the balancing of dyadic coopetitive relationships. Implications for organisations' coopetitive capabilities and how coopetitive relationships can be managed are also discussed.